Association Between Doppler Snuffbox Resistive Index and Tissue Perfusion in Septic Patients. Issue 6 (December 2020) - Wang, Cui; Wang, Xiaoting; Zhang, Hongmin; Su, Longxiang; Huang, Wei; Liu, Dawei
ABSTRACT: Background: Peripheral vascular disorders leading to tissue hypoperfusion play a central role in the pathophysiology of organ failure in septic shock. The Doppler snuffbox resistive index (SBRI) can be an accurate parameter to evaluate the status of peripheral vasculature at the bedside. We evaluated whether the SBRI is related to lactate levels or the peripheral perfusion index (PI) and its ability to predict lactate clearance in septic patients. Methods: We conducted a prospective observational study in a tertiary general and teaching hospital in China. From July 2019 to December 2019, all consecutive adult patients with septic shock who required intensive care unit admission were included. At the same time, 20 stable postoperative patients were studied as a control group. We recorded the hemodynamic parameters, including the SBRI and PI, which were measured simultaneously after patient recruitment. Results: We evaluated 44 patients with septic shock in the study group and 20 stable postoperative patients in the control group. Patients with septic shock had higher Sequential Organ Failure Assessment scores, procalcitonin levels, cardiac index (CI) and lactate levels than patients in the control group. The SBRI was correlated with the PI and lactate level. The CI was not correlated with lactate level in the patients examined. Based on lactate clearance in the first 6 h, the septic shock patients were divided into two groups: one with lactate clearance ≥20% (n = 28) and the other with lactate clearance <20% (n = 16). The CI was not significantly different between the two groups. The SBRI of the lactate clearance <20% group was higher than that of the lactate clearance ≥20% group and the control group. The PI of the lactate clearance <20% group was lower than that of the lactate clearance ≥20% group and the control group. The SBRI cutoff value for predicting 6-h lactate clearance after resuscitation was ≥1.09, with a sensitivity of 68.8% and a specificity of 85.7%. The PI cutoff value for predicting 6-h lactate clearance after resuscitation was ⩽0.99, with a sensitivity of 64.3% and a specificity of 81.2%. The SBRI was significantly better than the PI for predicting 6-h lactate clearance after resuscitation (area under the curve: 0.805 vs. 0.703, P  < 0.05). Conclusions: The Doppler SBRI is correlated with tissue perfusion parameters in critically ill patients. An abnormal SBRI may be better than the PI for predicting poor lactate clearance in septic patients. Further investigations are required to determine whether correcting an abnormal SBRI and PI may improve the success rate of septic shock resuscitation.